2022
DOI: 10.3389/fimmu.2022.854432
|View full text |Cite
|
Sign up to set email alerts
|

CD160 Promotes NK Cell Functions by Upregulating Glucose Metabolism and Negatively Correlates With HIV Disease Progression

Abstract: Natural killer (NK) cells are crucial for immune responses to viral infections. CD160 is an important NK cell activating receptor, with unknown function in HIV infection. Here, we found that CD160 expression was reduced on NK cells from HIV-infected individuals and its expression was negatively correlated with HIV disease progression. Further, GLUT1 expression and glucose uptake were higher in CD160+ NK cells, and the results of RNA-seq and flow cytometry demonstrated that CD160 positively regulated glucose me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…NK cells have been reported to use glycolysis and oxidative phosphorylation (Oxphos) pathways to provide energy for various physiological activities, such as activation and proliferation[47, 48]. We found that the glycolysis of □ Mtb -activated NKcells is significantly reduced, and this may explain the decline of IFN-□ production due to the growing consensus that glycolysis is critical for IFN- production by NK cells [49].…”
Section: Discussionmentioning
confidence: 98%
“…NK cells have been reported to use glycolysis and oxidative phosphorylation (Oxphos) pathways to provide energy for various physiological activities, such as activation and proliferation[47, 48]. We found that the glycolysis of □ Mtb -activated NKcells is significantly reduced, and this may explain the decline of IFN-□ production due to the growing consensus that glycolysis is critical for IFN- production by NK cells [49].…”
Section: Discussionmentioning
confidence: 98%
“…NK cells have been reported to use glycolysis and oxidative phosphorylation (Oxphos) pathways to provide energy for various physiological activities, such as activation and proliferation [ 46 , 47 ]. We found that the glycolysis of γ Mtb -activated NK cells was significantly reduced, and this may explain the decline in IFN-γ production due to the growing consensus that glycolysis is critical for IFN-γ production by NK cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CD160 is also implicated in the regulation of NK-cell metabolism. It was reported that CD160 expression is positively correlated with the expression of the glucose transporter (GLUT1) and glucose uptake in NK cells, which is indispensable for NK-cell functioning and IFN-γ secretion ( 14 , 78 ). CD160 expression in NK cells upregulates glucose metabolism through the activation of the AKT/mTOR/s6k signaling pathway ( 14 ).…”
Section: General Characteristics Of Cd160mentioning
confidence: 99%
“…It was reported that CD160 expression is positively correlated with the expression of the glucose transporter (GLUT1) and glucose uptake in NK cells, which is indispensable for NK-cell functioning and IFN-γ secretion ( 14 , 78 ). CD160 expression in NK cells upregulates glucose metabolism through the activation of the AKT/mTOR/s6k signaling pathway ( 14 ). In addition, mTORC1 signaling was previously demonstrated to be required for the upregulation of GLUT1 expression and the expression of glycolysis rate-limiting enzymes such hexokinase 2 and lactate dehydrogenase A, which enhance glucose uptake and glycolysis and increase NK-cell functioning ( 79 ).…”
Section: General Characteristics Of Cd160mentioning
confidence: 99%
See 1 more Smart Citation